y-11=-10

Simple and best practice solution for y-11=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-11=-10 equation:


Simplifying
y + -11 = -10

Reorder the terms:
-11 + y = -10

Solving
-11 + y = -10

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + y = -10 + 11

Combine like terms: -11 + 11 = 0
0 + y = -10 + 11
y = -10 + 11

Combine like terms: -10 + 11 = 1
y = 1

Simplifying
y = 1

See similar equations:

| (5p^3)(-m^8p^2)= | | -5x+17=-20x-18 | | p=s-14 | | 36x+200=76x | | x-11=5x | | 12x-4=96x-12 | | y=3x+-8 | | 4(x-y)(x-y)-25= | | 26x+9=8x+39 | | b+10=-13 | | 8=vu | | 3a-3=4a-1.5 | | x^2-18=19 | | (9-y)(4y+6)=0 | | 17+26x=30 | | -2x^2-x-3=0 | | 14-t=-10 | | 8.26x+4=68.2276+2x | | y=-.2x+12 | | 14.95-7.55= | | 13-k=5 | | 3/4x-7/4=8 | | 14r+12r=832 | | 9x+2=27x | | 5.7(x-1)=-0.3+42.3 | | -3y-2=-2y | | -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 | | 11-x+3=3n+3n | | G(t)=t+5 |

Equations solver categories